IMPLEMENTASI KURIKULUM 2013 PADA PEMBELAJARAN TEMATIK-INTEGRATIF DI SEKOLAH DASAR - Rusita Purnamasari; Purnomo, Heru (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
The 2013 curriculum is a complement to the previous curriculum, namely KTSP. With the emergence of the 2013 curriculum, there are issues in the form of pros and cons. Writing this article aims to find out how the implementation of the 2013 curriculum in thematic-integrative learning at the elementary school level. The method used in the research is literature review by searching journals, while other sources are obtained from books, laws, and government regulations. The results obtained from this literature review are the implementation of the 2013 curriculum, the things that support the successful implementation of the 2013 curriculum, the implementation of thematic-integrative learning, and also the obstacles faced in implementing the 2013 curriculum in thematic-integrative learning in elementary schools.